ANALISIS GOOGLE CLASSROOM BERDASARKAN PERSEPSI SISWA/I DI SMK NEGERI 44 JAKARTA MENGGUNAKAN METODE SUS DAN WEBUSE - Neyna Zahra Nur Karimah; Wulan Dari (Jurnal Mahasiswa Sistem Informasi (JMSI), 2025)
The shift in learning paradigms following the pandemic has driven massive adoption of digital platforms, one of which is Google Classroom. Although widely used across educational institutions, few studies have systematically evaluated its usability based on direct user perceptions, particularly among secondary school students. This study aims to assess the usability of Google Classroom at SMK Negeri 44 Jakarta using two standardized methods: the System Usability Scale (SUS) and the Website Usability Evaluation Tool (WEBUSE). Data were collected from 86 respondents through quantitative questionnaires and qualitative open-ended feedback. The results show that the average SUS score was 70.2, categorized as “Marginal High,” while the average WEBUSE score was 71.25%, classified as “Good.” Validity and reliability tests confirmed that all items in both instruments were valid and reliable. Open-ended responses revealed issues such as difficulties uploading files, limited communication features, and an unappealing interface. Overall, Google Classroom is considered sufficiently feasible as an online learning platform, yet requires further development to enhance user comfort and effectiveness